EKSISTENSI DINAS SOSIAL DAN TENAGA KERJA KOTA BINJAI DALAM PENANGGULANGAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) DI KOTA BINJAI - Ely Anista Br Ginting (Universitas Medan Area, 2015)
One important thing is the handling of Disability Issues Social Welfare, the Department implemented the social and labor Binjai City, is in order to minimize the amount Persons with social welfare problems Social welfare programs implemented in the hope of becoming an alternative solution to the problem of social welfare. Discussion, the results obtained in this study that the program is executed quite well, and the lack of significant issues or problems, although with limited budget priorities being able to anticipate through the program, so the limitations but showed positive performance. The problems of this study is the extent of the Department of Social and Manpower reduction task Binjai City social welfare problem in the city of Binjai, relating to the efficiency and effectiveness orgsanisasi.